Perceived risk for screen-detectable cancers among american indian adults in the zuni pueblo, USA: Insights and implications for intervention programs - Deborah Kanda; Kate Cartwright; V. Shane Pankratz; Judith Sheche; Mikaela Kosich; Nicholas Edwardson; Samantha Leekity; Shiraz I. Mishra (Preventive Medicine Reports)
Background: Perceptions of disease risk play an important role in adopting healthy behaviors. The main objective of this study is to examine factors associated with high perceived cancer risk among Zuni Adults in New Mexico, USA. Methods: We used data from a survey conducted in Zuni Pueblo from October 2020 to April 2021. Our analysis included 254 adults ages 21–75 years without a reported personal cancer history. Perceived cancer risk was determined from the question: “Compared to other people your age, how likely do you think it is that you could get cancer?” and ordinal logistic regression analyses were used to identify factors associated with high perceptions of cancer risk. Results: Overall, 35 %, 27 %, and 38 % of respondents reported perceived cancer risks that were lower than, about the same as, and higher than those of other people their age, respectively. From bivariate analysis, factors associated with high perceived cancer risk included: positive family cancer history (odds ratio [OR] = 1.95; 95 % confidence interval [CI]: 1.23–3.11), higher knowledge of cancer risk factors (OR = 1.45; CI: 1.09–1.93), higher education (OR = 1.46; CI: 1.16–1.84), and higher body mass index (OR = 1.44; CI: 1.07–1.94). In multivariable analysis, family cancer history (OR = 1.81; CI: 1.10–2.99), knowledge of risk factors (OR = 1.38; CI: 1.03–1.86), and education (OR = 1.81; CI: 1.10–2.96) remained statistically significant. Conclusion: Our findings provide important insights on perceptions of cancer risk in this community, and have important implications for developing effective, culturally relevant interventions in this community.